Teknik Penilaian Multidimensi untuk Mengevaluasi Keberlanjutan Pengelolaan Hutan Mangrove di Pulau Kangean Provinsi Jawa Timur - Aang Kuvaini; Aceng Hidayat; Cecep Kusmana; Sambas Basuni (Jurnal Wilayah dan Lingkungan, 2019)
Mangrove forests in Kangean Island have ecological, economic and social functions and benefits that must be managed to ensure the sustainability of mangrove forests. This study aims to determine the status of sustainability of mangrove forest management in Kangean Island. The research method used the Multidimensional Scaling (MDS) approach through the Rapid Apraisal for Kangean Mangrove Forest (Rap-KMforest) technique, to evaluate the sustainability of mangrove forests in a multidimensional manner. The results showed that the sustainability status of mangrove forest management in Kangean Island are varied, included the moderately sustainable category (51.40) on the ecological dimension, lack of sustainability (45.50) on the economic dimension, lack of sustainability (36.95) on the social dimension, and moderately sustainable (51.32) on the institutional dimension. Lever attributes whose effects are very sensitive to the sustainability of mangrove forest management are: (1) canopy density; (2) types of land use; (3) market of mangrove forest products; (4) funding of CSR support; (5) social conflict; (6) level of community education; (7) community knowledge about mangrove forests; (8) education about mangrove forests; (9) involvement of community institutions in mangrove management; and (10) formal institutional performance in mangrove management.